2005
DOI: 10.1007/s11104-004-4682-6
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi (Neotyphodium coenophialum) affect the growth and mineral uptake, transport and efficiency ratios in tall fescue (Festuca arundinacea)

Abstract: Neotyphodium coenophialum interacts mutualistically with its host grasses. Tall fescue (Festuca arundinacea Schreb.) plants infected by the fungal endophyte, Neotyphodium coenophialum (Morgan-Jones and Gams) Glenn, Bacon and Hanlin, often perform better than non-infected plants, especially in limited resource environments. However, there is a scarcity of information about endophyte-grass ecotypes interaction in Andisols of temperate regions. Clones of three tall fescue ecotypes (Fukaura, Koiwai and Showa) eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…In other studies, HiMag provided about 20% more leaf Mg than its parents, KY31 and MO96, on both acidic Typic Hapludults in Georgia (Wilkinson and Mayland 1997) and a calcareous Durinodic Xeric Haplocalcid soil in Idaho (Mayland and Sleper 1993). Different ecotypes of tall fescue in Japan produced different K, Ca, and Mg transport efficiencies (Rahman and Saiga 2005).…”
Section: Cultivar Effectsmentioning
confidence: 99%
“…In other studies, HiMag provided about 20% more leaf Mg than its parents, KY31 and MO96, on both acidic Typic Hapludults in Georgia (Wilkinson and Mayland 1997) and a calcareous Durinodic Xeric Haplocalcid soil in Idaho (Mayland and Sleper 1993). Different ecotypes of tall fescue in Japan produced different K, Ca, and Mg transport efficiencies (Rahman and Saiga 2005).…”
Section: Cultivar Effectsmentioning
confidence: 99%
“…Tall fescue is an important cool-season perennial forage grass commonly used for turf and soil conservation around the world (Rahman and Saiga 2005;Spyreas et al 2001;Stuedemann and Hoveland 1988). It covers a significant area of the eastern USA, and is increasingly prevalent in Africa, Australia, China, New Zealand, and South America, (Rudgers and Clay 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Endophyte existence in grass populations varies between species and genotypes (Schulthess and Faeth 1998) and between natural and agricultural grass populations (Faeth 2002). Endophyte infected tall fescue often has higher productivity than noninfected plants, especially in drought environments (Rahman and Saiga 2005). Malinowski and Belesky (2000) reported that host plants have better persistence and increased tolerance to biotic and abiotic stresses because of the association between plants and the endophyte.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced root surface area and root exudate activity were introduced as two responsible mechanisms of P deficiency tolerance in endophyte-infected tall fescue (Malinowski et al 1998a(Malinowski et al , 1999. Rahman and Saiga (2005) documented vegetative growth and nutrient acquisition in tall fescue varying with ecotype and modified by abiotic (soil fertility status) as well as biotic (endophyte infection) factors.…”
Section: Introductionmentioning
confidence: 99%